Indigenous knowledge of herbal medicines in Bangladesh. 3. Treatement of skin diseases by tribal communities of the hill tracts districts (Bangladesh Journal of Botany, 2011)
Indigenous knowledge of herbal medicines for skin diseases like boils, eczema, scabies, septic abscess, itching and skin allergy, burns, chicken pox, warts and leucoderma, fungal and bacterial infections, including healing cuts and wounds has been documented by randomly interviewing Chakma, Marma and Tanchunga tribes of the Hill Tracts districts of Bangladesh since 1995. The plant parts of 60 species belonging to 40 families were known to be used. The plant specimens were collected, identified and preserved at the Herbarium of Chittagong University. An enumeration of these plants is presented along with their tribal names, categories of skin diseases, plant parts with preparation and route of administration. Key words: Indigenous knowledge; Herbal medicines; Skin diseases; Tribes; Bangladesh DOI: 10.3329/bjb.v39i2.7303 Bangladesh J. Bot. 39(2): 169-177, 2010 (December)